Contribution for a better understanding of the technological sustainability in electrical energy production through photovoltaic cells - Mendes, R. P. (2011)
The conversion of solar energy into electricity reveals a huge importance in the production of “clean” energy, mainly when applied to decentralized production systems (micro-generation). However, there is the need to develop and optimize these processes in order to turn it more sustainable in economic and technological scoops. The main purpose of this work is to study the solar energy conversion into electricity through photovoltaic cells, characterizing the process efficiencies. This study intends to evaluate the energetic and exergetic efficiencies defining them as indicators in the formulation of a sustainability index. All the procedures are in a theoretical scope with an illustrative example in the end of this work.